Analisis Proses Produksi Sepatu dalam Perspektif Manajemen Operasional di PT. XYZ - Mufatikhatun Risqiyanti; M. Masrukhan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the shoe production process from an operational management perspective at PT. XYZ. The focus of the research is directed at the stages of the production process and the management of raw materials in supporting the smooth running and efficiency of production activities. This research uses a descriptive qualitative approach carried out through an Internship Experience Practice (PPL) at PT. XYZ. Data was collected through direct observation of production activities, interviews with relevant parties in the production department, and supporting documentation. The data obtained was analyzed by describing the production process flow, raw material management system, and production process control, then linked to the concept of operational management. The results showed that the shoe production process at PT. XYZ consisted of several interrelated stages, starting from raw material management to the main production process. The company has implemented a fairly structured operational management system, characterized by the recording of raw materials, the separation of materials by type, and the application of the First in First Out (FIFO) method to maintain material quality and smooth production. However, several operational obstacles were still found, such as limited production time, suboptimal coordination between departments, and the potential for defective products in the production process. The implementation of operational management at PT. XYZ has supported the shoe production process quite effectively, particularly in raw material management and production control. Nevertheless, improved coordination and continuous evaluation of the production process are needed to enhance operational efficiency and product quality.